Scientific Fundamentals Of The Propane-Butane Fraction Pyrolysis Process (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
This study investigates the pyrolysis of propane-butane fractions at high temperatures in an oxygen-free environment, focusing on primary reactions such as dehydrogenation, thermal cracking, radical cleavage, and aromatisation. Secondary processes, including olefin dimerisation, alkylation, and dehydroaromatization, were assessed via Gibbs free energy (∆G°) analysis. Thermodynamic results showed that aromatisation becomes favourable around 900–1000 °C, while hydrogen release occurs above 1100 °C. Brønsted and Lewis acid sites in high-silica mesoporous zeolites significantly influence catalytic activity. Higher SiO₂/Al₂O₃ ratios reduce Brønsted site strength, lowering reaction rates and olefin selectivity. Kinetic compensation and isokinetic behaviour indicate mechanistic similarity across catalysts. The findings are relevant for improving olefin yields and energy efficiency in propane-butane pyrolysis processes.